Comparative Analysis of Spoken Language Use in Formal and Non-Formal Communication: A Study of Eighth-Grade Students at MTsN 1 Mukomuko, Indonesia - Elvira Elvira; Ahmad Suradi; Dina Putrsi Juni Astuti (JPI: Jurnal Pustaka Indonesia, 2024)
Spoken language competence is essential for students to adapt to different social and academic contexts, yet many learners face challenges in shifting between formal and non-formal communication registers. This study aimed to analyze differences in spoken language use between formal and non-formal communication contexts among eighth-grade students at MTsN 1 Mukomuko. Using a quantitative ex post facto design, data were collected from 62 students, consisting of 17 in formal situations and 45 in non-formal situations, through questionnaires, observations, documentation, and interviews. The instruments were validated through Pearson’s Product-Moment correlation and achieved strong reliability with a Cronbach’s Alpha coefficient of 0.848. Data were analyzed using descriptive and inferential statistics, including tests of normality, homogeneity, and independent-sample t-tests with a significance threshold of p < 0.05. The results revealed a significant difference in students’ spoken language performance between the two contexts, with higher mean scores observed in non-formal situations (M = 31.46) compared to formal situations (M = 28.70), and the t-test result (t = -2.226, p = 0.030) confirmed the hypothesis. These findings indicate that students display more flexible, expressive, and spontaneous linguistic patterns in non-formal communication, whereas formal contexts require structured and rule-based expression. The novelty of this study lies in its systematic comparison of formal and non-formal spoken language within the same population, offering insights rarely addressed in Indonesian educational research. The implications suggest that educators should design balanced pedagogical strategies that foster both formal accuracy and non-formal fluency to strengthen students’ overall oral communication skills.